Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Penggunaan SPaylater pada Generasi Z di Kecamatan Magersari Kota Mojokerto - Dwi Silvialorensa, Dina; Hartono, Hartono; Heru Dwihandoko, Toto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Researchers know that many generation Z use SPaylater to make purchase transactions on the Shopee application. The types of products purchased are not all basic necessities, but they follow current trends and some even buy items because they are cute. The use of SPaylater can be influenced by the lifestyle of generation Z who follow trends without measuring their abilities. Therefore, financial literacy is really needed by society, especially generation Z. From this background, this research was conducted with the title